Training load, physical performance, biochemical markers, and psychological stress during a short preparatory period in brazilian elite male volleyball players - Horta, G. A. T.; Bara Filho, G. M.; Coimbra, R. D.; Miranda, R.; Werneck, F. Z. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to assess the relationship between training load (TL) and physical performance, biochemical markers, and psychological stress during a short preparatory period (SPP) in Brazilian elite male volleyball players. Twelve volleyball players from a team competing in the Brazilian Men's Volleyball Super League were enrolled (26.9 ± 4.6 years). Countermovement jump (CMJ), creatine kinase (CK), testosterone (T), cortisol (Cr), T/Cr ratio, and Recovery and Stress Questionnaire for athletes (RESTQ-Sport) were collected at baseline, after second, fourth, and sixth week. Training load was quantified daily using the rating of perceived exertion. Differences were noted between total weekly training load (TWTL) (F3,33 = 50.907; p = 0.0001), CK (F3,33 = 16.157; p = 0.0001), and T (F3,33 = 3.283; p = 0.03). No differences were seen in CMJ (F3,33 = 1.821; p = 0.16), Cr (F3,33 = 2.409; p = 0.08), or T/Cr ratio (F3,33 = 1.527; p = 0.23). The RESTQ-Sport demonstrated differences between moments in social stress (F3,33 = 2.297; p = 0.04; n hoch 2 = 0.25), success (F3,33 = 4.350; p = 0.01; n hoch 2 = 0.19), general well-being (F3,33 = 4.465; p = 0.01; n hoch 2 = 0.36), and injury (F3,33 = 2.792; p = 0.05; n hoch 2 = 0.62). The results showed a significant correlations of small to moderate magnitude between TWTL and CK (r = 0.32; p = 0.05). In conclusion, a short PP in volleyball leads to increased TL, CK level, and psychological stress. Training load was related with the increase of CK, suggesting muscle damage without increased physical performance.